2022
DOI: 10.1002/jha2.573
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoplasmacytic lymphoma and marginal zone lymphoma involving bone marrow: A diagnostic dilemma. Useful clinicopathological features to accurate the diagnosis

Abstract: Lymphoplasmacytic lymphoma (LPL) and marginal zone lymphoma (MZL) frequently infiltrate the bone marrow with similar histologic and immunohistochemical characteristics posing diagnostic problems. Bone marrow biopsy specimens from 25 LPL and 16 MZL have been studied, correlating with clinical, laboratory parameters and the MYD88_p.L265P mutation. Paratrabecular and interstitial infiltration pattern, serum IgM paraprotein levels, and MYD88_p.L265P mutation were significantly more frequent in LPL. Nodular or intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Определяющей является экспрессия на опухолевых клетках CD19, CD20 и sIgM. Наибольшие трудности вызывает дифференциальный диагноз с лимфомой маргинальной зоны (ЛМЗ) [9]. Как правило, экспрессия CD5, CD10 и CD23 при ЛПЛ отсутствует, однако позитивность по отдельным антигенам не исключает диагноза.…”
Section: чтобы разрешить очевидное противоречие эксперты Icc-2022 опр...unclassified
“…Определяющей является экспрессия на опухолевых клетках CD19, CD20 и sIgM. Наибольшие трудности вызывает дифференциальный диагноз с лимфомой маргинальной зоны (ЛМЗ) [9]. Как правило, экспрессия CD5, CD10 и CD23 при ЛПЛ отсутствует, однако позитивность по отдельным антигенам не исключает диагноза.…”
Section: чтобы разрешить очевидное противоречие эксперты Icc-2022 опр...unclassified
“…Studies by Treon et al and other researchers suggested the MYD88 L265P mutation is present in >90% of WM, and that it could be important for the differential diagnosis of WM [8] vs. plasma cell malignancies. This mutation is also present in various other B-cell neoplasms such as SMZL, CLL, and DLBCL, but at a lower frequency [9][10][11][12][13]. Studies have shown that WM patients lacking the MYD88 L265P may be less responsive to Bruton's tyrosine kinase (BTK) inhibitors [14], which may also be associated with a lower number of tumor cells and lower International Prognostic Scoring System score at presentation [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is known as Waldenstroem’s macroglobulinemia (WM), when presenting with IgM paraproteinemia and bone marrow involvement [ 1 , 2 ]. However, (lympho)plasmacytic differentiation can also be found in other low-grade B-cell lymphomas, mainly in marginal zone lymphoma (MZL) or chronic lymphatic leukemia (CLL), but also in mantle cell lymphoma (MCL) [ 1 , 3 6 ]. Beside morphological characteristics, the immune phenotype may overlap between low-grade lymphomas, resulting in clear diagnostic complexities [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%